Full‐Parameter Omnidirectional Thermal Metadevices of Anisotropic Geometry. Issue 49 (11th October 2018) - Han, Tiancheng; Yang, Peng; Li, Ying; Lei, Dangyuan; Li, Baowen; Hippalgaonkar, Kedar; Qiu, Cheng‐Wei
Abstract: Since the advent of transformation optics and scattering cancelling technology, a plethora of unprecedented metamaterials, especially invisibility cloaks, have been successfully demonstrated in various communities, e.g., optics, acoustics, elastic mechanics, dc electric field, dc magnetic field, and thermotics. A long‐held captivation is that transformation‐optic metamaterials of anisotropic or noncentrosymmetric geometry (e.g., ellipsoids) commonly come along with parameter approximation/simplification or directional functions. Here, a synthetic paradigm with strictly full parameters and omnidirectionality is reported simultaneously to address this long‐held issue for molding heat flow and experimentally demonstrate a series of noncentrosymmetric thermal metadevices. It changes the usual perception that transformation thermotic/dc/acoustic metamaterials are just a direct and simplified derivatives of the transformation‐optic counterpart. Instead, the proposed methodology solves an intriguingly important and challenging problem that is not possibly achievable for transformation‐optic metamaterials. The approach is rigorous, exact, robust, and yet elegantly facile, which may open a new avenue to manipulating the Laplacian and wave‐dynamic fields in ways previously inconceivable. Abstract : A long‐held captivation is that transformation‐optic metamaterials of anisotropic or noncentrosymmetric geometry (e.g., ellipsoids) commonly come along with parameter approximation/simplification or directional functions. A synthetic paradigm with strictly full parameters and omnidirectionality is reported simultaneously to address this long‐held issue for molding heat flow, and a series of noncentrosymmetric thermal metadevices is experimentally demonstrated.